2018
DOI: 10.3233/jin-170045
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation based on quantitative electroencephalogram combining positive psychotherapy for major depression

Abstract: Frontal cortex activity is reduced in the left hemisphere during depression. Transcranial direct current stimulation is a noninvasive neuromodulation technique that can increase frontal cortex activity. Therapy based on transcranial Direct Current Stimulation and positive psychology therapy was applied for improving patients’ quality of life. The present study compared three conditions of subjects with clinical depression; (a) transcranial Direct Current Stimulation therapy, (b) positive psychotherapy, and(c) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In another recent clinical trial, researchers compared tDCS, positive psychotherapy, and combined strategy for the treatment of depression. 15 Nine women (mean age of 45 years) with resistant major depression were assigned randomly to 3 groups of equal size. For tDCS, 12 sessions of treatment with anodal stimulation of 1.5 mA for 15 minutes was administered over F4 or F3 areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another recent clinical trial, researchers compared tDCS, positive psychotherapy, and combined strategy for the treatment of depression. 15 Nine women (mean age of 45 years) with resistant major depression were assigned randomly to 3 groups of equal size. For tDCS, 12 sessions of treatment with anodal stimulation of 1.5 mA for 15 minutes was administered over F4 or F3 areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, while there are some studies with sufficient power, 13 there are other researches with poor methodological quality, lack of uniformity, and small sample sizes that decrease the generalizability of the conclusions. 14,15 We need less expensive and more beneficial methods for the treatment of patients with refractory major depression. Until reliable information about different therapeutic methods is collected, it is difficult to design the best intervention strategy for treatment-resistant depression.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term tDCS with 15 treatment periods has been found to affect mood and cognition in 50 and 60%, respectively, of individuals with depression (Al-Kaysi et al, 2017). Similarly, a lower-intensity (1 and 1.5 mA) tDCS protocol also resulted in reduced ERP (Shahsavar et al, 2018) and power spectra (e.g., delta, theta, and alpha frequency bands) (Palm et al, 2009;Khayyer et al, 2018) following stimulation. In particular, combined treatment with positive psychotherapy and tDCS can significantly affect depression.…”
Section: Depressive Disordermentioning
confidence: 98%
“…In particular, combined treatment with positive psychotherapy and tDCS can significantly affect depression. Effects are more pronounced following 3 months of follow-up than with the use of tDCS alone ( Khayyer et al, 2018 ).…”
Section: Depressive Disordermentioning
confidence: 99%
“…Additionally, most clients suffering from depression have low levels of self-compassion (Krieger, Altenstein, Baettig, Doerig, & Holtforth, 2013). Scholars have found that psychological interventions decrease symptoms of depression and improve clients' selfesteem (Khayyer, Ngaosuvan, Sikström, & Ghaderi, 2018). Hence, clients, such as depressed parents of ADHD children, may benefit from interventions aimed at aspects of self-compassion (Wong & Mak, 2013).…”
mentioning
confidence: 99%